2014
DOI: 10.4067/s0717-95022014000300024
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Determine the Size of Biometric Differences in the Skull of Two Colour Variants of American Mink (Neovison vison)

Abstract: An attempt to determine the size of biometric differences in the skull of two colour variants of American mink (Neovison vison).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In their study, Lynch and Hayden [12] also point out to genetic determination of body size, which is associated with corresponding genes for coat colour. Similar results were obtained by Baranowski et al [1] who found a relationship between the size and shape of the skull and the colour variant of American minks.…”
Section: Discussionsupporting
confidence: 80%
“…In their study, Lynch and Hayden [12] also point out to genetic determination of body size, which is associated with corresponding genes for coat colour. Similar results were obtained by Baranowski et al [1] who found a relationship between the size and shape of the skull and the colour variant of American minks.…”
Section: Discussionsupporting
confidence: 80%
“…On the other hand, more intensive breeding with the increasingly frequent use of mutations may lead to far-reaching changes in general health status of animals. In American minks kept under human control and undergoing selective pressure, there have been a change in the morphological type (Kruska, 2005;Baranowski et al, 2014), as well as a number of coat coloration mutations, as a typical consequence of their domestication (Castle & Moore, 1946). This requires paying attention to the possibility of side effects of one-sided selection and raising awareness to the effect of mutations on the cardiac status.…”
Section: Introductionmentioning
confidence: 99%